Answer:
Step-by-step explanation:
Answer C (x + 1) is correct; if we let x + 1 equal 0, we get the root (x-intercept) -1, which appears on this graph
X + 1 must be a factor of the polynomial graphed
How to find the factor
The factor is solved using the points where the graph intersects the x-axis.
This points are called the roots
Examining the graph the roots are x = -1 and x = 4
Hence x + 1 must be a factor
Six times a number increased by 26 is 296
What is the number?
Answer:
x = 45
Step-by-step explanation:
6x+26 = 296
6x+26-26 = 296-26
6x = 270
x = 45
Answer:
45
Step-by-step explanation:
Write the equation:
6n+26= 296
Subtract 26 from both sides:
6n+26-26= 296-26
Simplify:
6n= 270
Divide 6 by each side to get n by itself:
6n/6= 270/6
Simplify:
n= 45
15x – 7 = 4x – 18
What is x
Answer:
x = - 1
Step-by-step explanation:
Given
15x - 7 = 4x - 18 ( subtract 4x from both sides )
11x - 7 = - 18 ( add 7 to both sides )
11x = - 11 ( divide both sides by 11 )
x = - 1
Which equation can be used to find the volume of this solid? 6 in 7 in
8 in
V=7+6/2x8. V=7+6+8/2. V=7x6/2x8. V=7x6/2+8
Answer:
V=7+6+8/2
Step-by-step explanation:
9219 divided by 76. will someone pls answer this?
Answer:
121.302632
Step-by-step explanation:
Answer:
121.302632
Step-by-step explanation:
Use a calculator
Lana and Jeff each randomly surveyed 15 students about their favorite types of movies. What would you expect to see in the samples? Select all that apply.
A: different members are found in each sample
B: some members may possibly overlap in each sample
C: each sample gave the same responses
D: both samples would be representative of the population
E: both samples include only Lana and Jeff friends
SELECT ALL THAT APPLY
Option (A),(B)and ,(D) will apply
Lana and Jeff each randomly surveyed 15 students about their favorite types of movies. There can be three possibilities viz"
Different members are found in each sample,some members may possibly overlap in each sample,both samples would be representative of the population
Explanation:
Lana and Jeff selected the sample randomly. A Random sample is one where equal chances are given to everyone. It is selected in an unbiased manner.
There can be many possibilities in the selection of a sample of 15 students to study their favorite movies. Like:
Different members are found in each sample- the Lana and Jeff might select a sample from their own sources. So it might include different members.Some members may overlap- if Lana And Jeff are related then some of their members might be the same.Both samples would be the representative of the population- Sample would tell us about the entire population.
Stop cheating on Pearson asking for answers, kid.
Find the volume of the regular pyramid.
A. 588.8 m^3
B. 235.52 m^3
C. 706.56 m^3
D. 1766.4 m^3
Answer:
I think it is A.
Step-by-step explanation:
Answer:The Answer is A.
Step-by-step explanation:
Write an expression that is equivalent to z + z + z+ z.
Enter your answer in the space provided.
Answer:
4z
Step-by-step explanation:
brainliest please
z+z+z+z
=4z
Hope it will help u...
The following data set represents the number of students in the Tuesday
trampoline classes. Which of the following represents the interquartile range?
9, 5, 14, 6, 8, 9, 6, 2, 3, 5
D is the correct answer.
1/3x + 8x^4 - 2/3x^2 - x in standard form
Answer:
8x^{4}-2/3x^{2}-2/3x
Step-by-step explanation:
Which of these numbers is in the solution set of 7x = 56? A. 9 B. 6 C. 7 D. 8
[tex]Answer:x=8[/tex]
Divide both sides by 7
[tex]7x/7=56/7\\x=8[/tex]
which is the graph of the linear function that is represented by the equation y = 1/2 x 2
Answer: I believe it’s c
What is the value of x in the system of equations shown below?
5x + 4y= 1
Y= 1 -x
Answer:
The solution to this system of equations is x = -3 and y = 4.
Step-by-step explanation:
In order to solve this system we will use the second equation, which have the "y" isolated on the left side and use that value for "y" in the first equation. This is shown bellow:
5x + 4(1 - x) = 1
5x + 4 - 4x = 1
5x - 4x = 1 - 4
x = -3
Now we can use the value we found for x in the second equation to determine y.
y = 1 - x
y = 1 - (-3) = 1 + 3
y = 4
So the solution to this system of equations is x = -3 and y = 4.
45/200 x + x = 3920
what does x equal?
Answer:
3/52528
Step-by-step explanation:
Is that (x) times x + x ?
If so, x = 3,200
45/200 (x) x+x =3920
45 divided by 200 times x (3,200) plus x(3,200) equals 3920.
I hoped that helped !
What is 2 to the 500 power
Answer:
thats an error??
Step-by-step explanation:
Answer:
3.273391e+150
Step-by-step explanation:
Use a calculator
You roll two number cubes. What is the probability of rolling double threes?
The probability of rolling double threes with two number cubes is calculated by multiplying the likelihood of each die showing a three independently, which is 1/6. Since each die is independent, the combined probability is 1/6 x 1/6 or 1/36.
When rolling two number cubes, often referred to as dice, the probability of rolling double threes is determined by considering the likelihood of each event occurring independently. Each die has six faces, so the probability of rolling a three-on-one die is 1/6. Since the outcome of rolling the second die is independent of the outcome of the first die, its probability of showing three is also 1/6.
The combined probability of both independent events occurring—that is, rolling a three on both dice—is found by multiplying the probabilities of the individual events. This means the probability is 1/6 multiplied by 1/6, which equals 1/36. So, the chance of rolling double threes is 1/36.
If we were discussing a different combination, such as rolling a one and a three, we would add the probability of the first die rolling a one and the second a three to the probability of the first die rolling a three and the second a one. But in the case of double threes, there is only one possible outcome that meets the criteria (a three on the first die and a three on the second) and therefore only one product of probabilities to consider.
What is the equation of its axis of symmetry?
Answer:
x=-7
Step-by-step explanation:
Answer:
Step-by-step explanation:
hello :
x= -7Find the solution to the following system using substitution or
elimination:
y = 2x - 1
y = 5x - 7
of 5
(-2,-5)
(2,3)
( 6/7,5/7)
(1,1)
Answer:
(2,3)
Step-by-step explanation:
Substitute y = 2x - 1 in the equation y = 5x - 7
2x - 1 = 5x - 7
2x - 1 + 7 = 5x
2x + 6 = 5x
6 = 5x - 2x
6 = 3x
3x = 6
x = 6/3
x = 2
Substitute the value of x in, y = 2x - 1
y = 2*2 - 1
y= 4 - 1
y = 3
Help please! Will give brainly!
4x+1=3
Can you give me a value for x that makes this equation false?
For this equation, x = 1/2 makes it true.
4x + 1 = 3
To find a value for x that makes this equation true, we need to find a value where 4x + 1 equals 3.
4x + 1 = 3
Subtracting 1 from both sides:
4x = 2
Dividing both sides by 4:
x = 2/4
Simplifying:
x = 1/2
Substituting x = 1/2 into the equation:
4 . 1/2 + 1 = 3
2 + 1 = 3
3 = 3
Question
Mosi is putting together his monthly budget and would like to know how much he makes in a month. His annual net salary is
$52,000. What is his monthly pay rate, rounded to the nearest dollar?
Final answer:
Mosi's monthly pay rate, calculated from his annual net salary of $52,000 and divided by 12 months, is $4,333 when rounded to the nearest dollar.
Explanation:
To calculate Mosi's monthly pay rate from his annual net salary, we need to divide his total annual net income by the number of months in a year. Since Mosi's annual net salary is $52,000, we perform the following calculation:
Monthly Pay Rate = Annual Net Salary ÷ Number of months in a year
Monthly Pay Rate = $52,000 ÷ 12
The result is a monthly pay rate of $4,333.33. However, the question asks us to round to the nearest dollar. Therefore, Mosi's monthly pay rate is $4,333 when rounded to the nearest dollar.
how to find the average rate of change for f(x)=2^x;[2,4]
Answer:
6
Step-by-step explanation:
The average rate of change over the interval [tex][a,b][/tex] for a function [tex]f[/tex] is [tex]\frac{f(b)-f(a)}{b-a}[/tex].
So the average rate of change for [tex]f(x)=2^x[/tex] on [tex][2,4][/tex] is:
[tex]\frac{2^4-2^2}{4-2}=\frac{16-4}{2}=\frac{12}{2}=6[/tex].
What should be substituted in a linear equation in order to solve it
Answer:
A value for x.
Step-by-step explanation:
For example,
[tex]y=-3x+6[/tex]
Substitute a random number for x to find the value of y, after which you'll have a point.
x should be substituted in order to find y
A company that is averse to
? ao might lose out on opportunities to grow its business through innovation.
Answer:
Step-by-step explanation:
Just go to Google they have all the answers sorry I can't seem to understand your question
What is the sum of (-5x + 8) + (x2 – 10x)
Answer:
-13x+8
Step-by-step explanation:
add the x's including negatives
Answer:
-13x + 8
Step-by-step explanation:
Add the x's including the negatives
Which number is a rational number? V34 V13/16 V9/2 V49
Answer:
√49 = 7
Step-by-step explanation:
√49 = 7 is the only given number that is rational.
If the volume of a square pyramid is 6 km3
and
the height of the pyramid is 9 km, what is the
length of a side of the base?
A. √7 km
B. 54 km
C. 2 km
D. √2 km
PLEASE HELP
Answer:
The total divide by 7
A. √7 km
what is the area of the shaded region in square millimeters?
Answer:
Hi There the correct answer C 64.84
Step-by-step explanation:
Because all you really need to do to get the answer multiply and you get your answer from there.
Using Euler's Formula, given Edges = 12, Vertices = 8, how many Faces?
A.10
B.8
C.6
D.4
Answer:
C
Step-by-step explanation:
Euler's formula for polyhedra states that
F + V - E = 2 ( F is faces, V vertices and E edges ), thus
F + 8 - 12 = 2, that is
F - 4 = 2 ( add 4 to both sides )
F = 6
The number of faces is 6
Circle $O$ is located on the coordinate plane with center at $(2,3)$. One endpoint of a diameter is at $(-1,-1)$. What are the coordinates of the other endpoint of this diameter? Express your answer as an ordered pair.
To find the other endpoint of the diameter of a circle, you can use the midpoint formula in reverse with the given center and one endpoint. In this case, the coordinates of the other endpoint of the diameter are (5, 7).
The coordinates of the other endpoint of a diameter of a circle given that one endpoint and the center of the circle are known. We know the center of the circle, O, is at (2, 3) and one endpoint of the diameter is at (-1, -1). The diameter of a circle is a straight line through the center connecting two points on the circle. If you have one endpoint (x₁, y₁) and the center (x₂, y₂), the coordinates of the other endpoint (x₃, y₃) can be calculated using the midpoint formula in reverse:
x₃ = 2 × x₂ - x₁
y₃ = 2 × y₂ - y₁
For this circle:
x₃ = 2 × 2 - (-1) = 4 + 1 = 5
y₃ = 2 × 3 - (-1) = 6 + 1 = 7
So, the coordinates of the other endpoint of the diameter are (5, 7).
Point Z is the circumcenter of ΔLMN.
Point Z is the circumcenter of triangle L M N. Lines are drawn from each point of the triangle to point Z. Lines are drawn from point Z to each side to form right angles and line segments Z A, Z B, and Z C.
Which must be true?
Line segment A N is-congruent-to line segment L B
Line segment N C is-congruent-to line segment B Z
AngleBMZ Is-congruent-to AngleCMZ
AngleZBM Is-congruent-to AngleZCM
Answer: Option D.
Step-by-step explanation: I did this.
Answer:
Option D
Step-by-step explanation:
BECAUSE I KNOW!!!
L=U²A divided by (A+B)² make A the subject of formular
Answer:
A = [- 2Bl + U^2 +/- √((2BL - U^2)^2 - 4B^2L^2) ] / 2L
Step-by-step explanation:
L = U^2A / (A + B)^2
U^2 A = L(A^2 + 2AB + B^2)
U^2 A = LA^2 + 2ABL + B^2L
LA^2 + 2ABL - U^2A + B^2 L = 0
LA^2 + (2BL - U^2)A + B^2L = 0
Using the quadratic formula
A = [- (2BL - U^2) +/- √[(2BL - U^2)^2 - 4*L*B^2L] / 2L
A = [- 2BL + U^2 +/- √[(2BL - U^2)^2 - 4B^2L^2) ] / 2L